2017
DOI: 10.1002/wps.20420
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence, incidence and mortality from cardiovascular disease in patients with pooled and specific severe mental illness: a large‐scale meta‐analysis of 3,211,768 patients and 113,383,368 controls

Abstract: People with severe mental illness (SMI) -schizophrenia, bipolar disorder and major depressive disorder -appear at risk for cardiovascular disease (CVD), but a comprehensive meta-analysis is lacking. We conducted a large-scale meta-analysis assessing the prevalence and incidence of CVD; coronary heart disease; stroke, transient ischemic attack or cerebrovascular disease; congestive heart failure; peripheral vascular disease; and CVD-related death in SMI patients (N53,211,768) versus controls (N5113,383,368) (92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
838
4
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,273 publications
(930 citation statements)
references
References 138 publications
34
838
4
18
Order By: Relevance
“…However, the residual heterogeneity remained very large. Nevertheless, high heterogeneity is very common in meta‐analysis on pooled percentage . In addition, we performed a separate analysis of only the retrospective studies and found that the overall adherence rate was 13% less than when the prospective studies were included.…”
Section: Discussionmentioning
confidence: 88%
“…However, the residual heterogeneity remained very large. Nevertheless, high heterogeneity is very common in meta‐analysis on pooled percentage . In addition, we performed a separate analysis of only the retrospective studies and found that the overall adherence rate was 13% less than when the prospective studies were included.…”
Section: Discussionmentioning
confidence: 88%
“…Life expectancy is 15‐20 years shorter in patients with schizophrenia compared to the healthy population, with cardiovascular disease (CVD) as a main cause of increased mortality . There are indications that physical inactivity may be the origin for CVD development .…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with increased suicide risk, cognitive and functional impairments, development of Alzheimer's disease and vascular dementia, and with a higher burden of medical illnesses . Of particular concern among those with depression is the increased risk of cardiovascular disease, diabetes, and metabolic syndrome, with greater risk evident with increasing age.…”
Section: Introductionmentioning
confidence: 99%